EFEKTIVITAS E-LKPD BERBASIS PROJECT-BASED LEARNING (PjBL) PADA MATERI PERUBAHAN LINGKUNGAN UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK KELAS X SMA - Amanda Putri Dwi Wijaya; Winarsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Creative thinking is one of the essential 21st-century competencies that senior high school students need to master, yet classroom practice on environmental change material is still dominated by conventional, teacher-centered instruction that leaves students little room to design their own solutions to real environmental problems. This condition underlines the urgency of an interactive electronic student worksheet (e-LKPD) integrated with the Project-Based Learning (PjBL) model, which engages students directly in identifying problems, designing projects, and producing real solutions. This study examined the effectiveness of a PjBL-based e-LKPD on environmental change material in improving the creative thinking skills of tenthgrade students. A one-group pretest-posttest design was applied to 34 tenth-grade students of SMAN 1 Wonoayu, selected through purposive sampling, and effectiveness was determined by comparing pretest and posttest results using the N-Gain formula. The mean pretest score of 46.3 (low category) increased to a mean posttest score of 88.6 (very high category), producing an overall N-Gain of 0.78 (high category). Each creative-thinking indicator likewise showed high-category gains, with flexibility reaching 0.79, elaboration 0.80, and fluency 0.78. These findings confirm that the PjBL-based e-LKPD is effective for improving students' creative thinking skills on environmental change material and offers a relevant alternative to bridge the gap between 21st-century learning demands and current classroom practice.